If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7p + 1 = 5p + 25 Reorder the terms: 1 + 7p = 5p + 25 Reorder the terms: 1 + 7p = 25 + 5p Solving 1 + 7p = 25 + 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. 1 + 7p + -5p = 25 + 5p + -5p Combine like terms: 7p + -5p = 2p 1 + 2p = 25 + 5p + -5p Combine like terms: 5p + -5p = 0 1 + 2p = 25 + 0 1 + 2p = 25 Add '-1' to each side of the equation. 1 + -1 + 2p = 25 + -1 Combine like terms: 1 + -1 = 0 0 + 2p = 25 + -1 2p = 25 + -1 Combine like terms: 25 + -1 = 24 2p = 24 Divide each side by '2'. p = 12 Simplifying p = 12
| 10=5+2x | | 24x^2+36=4x*h | | 2(c-1)=4(3-c) | | 4x^2+36x=4x*h | | 6x+29x-7=7(5x+4) | | 3y+9=2y-6 | | 6x^2-7x+3=0 | | 3r+8=3 | | 3(2-x)=x+2 | | 4x+36x=4x*h | | 5q-5=17 | | 2(3n-1)=(4n+8)+7 | | 2.00-.33=.22x | | 2t+6=21-t | | 5(5x+2)-9=25x+1 | | 8c=90-c | | 11-5y=4y+20 | | 65-5x=4x+23 | | 47x+1673x-15=43(40x+60) | | 11+5y=4y+20 | | 4(t+2)=18-t | | x^2+3x-2x=5x+1 | | .6x-4.2=.6 | | 93-5x=8x-15 | | 4x-2=11x-54 | | -4(3x-1)+7(3-2x)= | | 3(4x+3)+99=17x+4-5x+104 | | 0.5x-6+2x+0.5x=12 | | -118-10x=10x+22 | | 8+6x=2x-32 | | 1/2(x+8)=14 | | 4350-3915=87(50x-45) |